2020
DOI: 10.1002/app.50122
|View full text |Cite
|
Sign up to set email alerts
|

Influences of high‐impact polystyrene loading on the foaming behavior andflame‐retardantproperties of polyphenylene oxide composites blown withCO2

Abstract: Polymeric foam with high expansion ratio, well-defined cell structure, and excellent flame retardant properties is essential for broadening its applications. Polyphenylene oxide (PPO) is a kind of cost-effective engineering plastic with excellent flame retardancy, anti-dripping behavior, and good mechanical strength, but suffers from its poor processability. In this study, microcellular PPO composite foams were fabricated by applying a solid-state foaming technology using compressed CO 2 as the blowing agent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Their results showed that the foam expansion rate of the PPO/HIPS blends increased, and the optimum foaming temperature range widened after HIPS addition. Furthermore, these foams exhibited exceptional thermal insulation and tensile properties 8 . Jiang et al Successfully produced PPO/HIPS bead foams with excellent compression, tensile, and flame retardant properties, using in‐mold foaming and mold forming technologies 9 …”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the foam expansion rate of the PPO/HIPS blends increased, and the optimum foaming temperature range widened after HIPS addition. Furthermore, these foams exhibited exceptional thermal insulation and tensile properties 8 . Jiang et al Successfully produced PPO/HIPS bead foams with excellent compression, tensile, and flame retardant properties, using in‐mold foaming and mold forming technologies 9 …”
Section: Introductionmentioning
confidence: 99%
“…A second compound, such as PA [ 16 ] , PBT [ 17 ] , and high‐impact PS (HIPS), [ 18 ] is usually used to blend with PPO to improve melt viscosity. Using temperature rising foaming method, Zhai et al [ 19 ] systematically studied the influence of the addition of HIPS on thermal behavior, foaming behavior, and flame‐retardant properties of PPO. It was found that 18−48% loading of HIPS greatly increased the expansion ratio of PPO/HIPS foams from 1.8−3.3 to 10.8−14.3.…”
Section: Introductionmentioning
confidence: 99%